(untitled) (Bangladesh Pharmaceutical Journal, 2023)
Litsea deccanensis Gamble. (Family: Lauraceae) is used traditionally for sprained or swollen joints such as ankles or knee. Still, there is no report for its analgesic activity, therefore the present study was aimed to evaluate analgesic activity of the crude methanolic extract of L. deccanensis (MELD) bark in various mice models. Acetic acid-induced writhing, Eddy’s hot plate and formalin induced paw licking tests were performed to evaluate the pain reducing/relieving effects. In acetic acid-induced writhing model, MELD showed significant reduction of squirming (p < 0.001, p < 0.01 and p < 0.05) in a dose dependent manner as compared to control. In the heat induced pain model (Eddy’s hot plate method), MELD showed a slight increment of the latency time for the initiation of the reaction in the experimental animals, that revealed a moderate analgesic activity of MELD when compared to control group, but the results were insignificant. Whereas, in the formalin induced pain model, the reaction time was decreased significantly (p < 0.05) with the increment of doses for the studied plant extract (MELD) as well as standard in the late phase (20-30 min) of the study. So, the present study concluded a significant reduction of acetic acid-induced squirming or writhing, and formalin induced biting or licking in mice, provided us the evidence of having pain reducing potential. Bangladesh Pharmaceutical Journal 26(2): 144-149, 2023 (July)